PENENTUAN LUAS PRODUKSI OPTIMUM PADA PERUSAHAAN MANUFAKTUR - -, Sunarso (Universitas Slamet Riyadi, 2008)
ABSTRACT To determine correct production volume a company needed is assorted of appliance which can be utilized to determine the production volume, one of the utilized by appliance break-even analysis. This analysis is utilized to know how big executed production volume in the company will be able to reach situation break-even. Wide determination of correct production will mean also company has strived more effective in exploiting available production factors. Wide determination of production very holding of important role in reaching target, that is maximum profit. Factors of production which allocation precisely is advantage from wide determination of real correct production, location goodness, raw material and also other factors of production. Other advantage that is can depress extravagance of financial, on that account wide determination of production, observation and planning represent main key. So that production process can be executed, require to be compiled by the way of, technique or method to create or add usefulness a goods by using sources or existing factors of production. Keywords: production capacities, break even point, linear programming,